Influence of local government on medium-sized enterprises: Uzbekistan and foreign experience - Bekchanov Davron Masharipovich, (THE INNOVATION ECONOMY, 2026)
This article examines the impact of local government authorities on the development of medium-sized enterprises (MSEs) in Uzbekistan through a comparative analysis. The study reviews legislative and institutional initiatives, financial support instruments, infrastructure and advisory services, as well as innovation programs. Uzbekistan’s experience is compared with the cases of Japan, South Korea, Italy, and Spain. The findings demonstrate that the effectiveness of local programs largely depends on the targeted and transparent allocation of resources. Furthermore, it is emphasized that innovation and financial support mechanisms successfully applied abroad should be adapted to the specific conditions of Uzbekistan.